El Control Interno Y Su Aplicabilidad En La Gestión Pública Del Orden Territorial Del Departamento De Caldas (2023)
This article was carried out with the purpose of knowing the applicability of internal control in the public management of the territorial order of the Department of Caldas, the importance of this investigation lay in knowing if the entities under study comply with internal control and in turn to be aware if the methodologies used are being effective to achieve the objectives set forth by the territorial entities, the conceptual framework is related to the study variables: Internal Control and the applicability in public management, based on authors such as Arens A, Elder R, Portal J and Camou among others.